China's Labor Market in the 'New Normal' - Lam, Waikei (IMF Working Papers; Working Paper ;, 2015)
As China implements reforms under the 'new normal,' maintaining stability in the labor market is a priority. The country's demography and labor dynamics are changing, after benefitting in past decades from ample cheap labor. So far, the labor market appears to be resilient, even as growth slows, driven in part by expansion of the services sector. Migrant flows and possible labor hoarding in overcapacity sectors may also help explain this. Yet, while the latter two factors help serve as shock absorbers- contributing to labor market stability in the short term-if they persist, they may delay the needed adjustment process, contributing to an inefficient allocation of resources and curtailing productivity gains. This paper quantifies to what extent structural trends and the reform pace affect employment growth under the new normal. Delays in reform implementation would weaken growth prospects in the medium term, running the risk that job creation will fall below policy targets, leading to labor market pressures in the future. In contrast, successful transition might require faster reforms, including in the overcapacity and state-owned enterprise sectors, supported by well targeted social safety nets.